The Design and Analysis of Invisible Radome with Sandwich-like Properties - Meng, Tianzhen; Wu, Weiwei; Yuan, Naichang (Společnost pro radioelektronické inženýrství, 2017)
A novel thin radome made by metamaterial is presented, with the properties like the sandwich where the middle acts as a pass band filter at an expected frequency band, while others behave as absorbers. This new radome consists of three layers including metal goblets-shape the frequency selective surface (FSS) layer, a substrate and a resistive square loops. Compared with the traditional invisible radome, the new radome’s two absorptive bands were separated by one transmission band, which is a challenge for the traditional ones. Except for the analysis of absorption property, the effects of the radome for the antenna are also simulated and some useful conclusions are drawn. Also, it has the advantages of simple structure for the easy fabrication, which could be more attracting in practical radome.
Keywords: Invisible radome; RCS reduction; resistive material.